FSH and bone: Comparison between males with central versus primary hypogonadism - Giovanelli, Luca; Quinton, Richard; Cangiano, Biagio; Colombo, Stefano; Persani, Luca; Bonomi, Marco; Chiodini, Iacopo (Frontiers in Endocrinology, 2022)
Objective: Experimental studies proposed a direct effect of FSH on the skeletal metabolism, but results of human studies mainly conducted in females are controversial. The present study aims to investigate the possible role of FSH excess in male bone health, by comparing for the first time primary and central hypogonadism. Design and Methods: 119 men were enrolled in this cross-sectional observational study at the time of the first diagnosis of hypogonadism. All participants had spontaneous pubertal development. Regarding patients with hypergonadotropic hypogonadism (Hyper-H), Klinefelters (KS) were distinguished from the other forms (non-KS-Hyper-H) based on the onset of FSH elevation. Bone mineral density (BMD) at both lumbar spine (LS) and femoral neck (FN), as well as the prevalence of morphometric vertebral fractures, were assessed. Results: Across the whole cohort, higher LS and FN BMD were associated with older age at diagnosis and higher body mass index (BMI), respectively. After adjusting for potential confounders (age at diagnosis, BMI, smoking habits, degree of hypogonadism defined by calculated free testosterone, and 25OH vitamin D levels), non-KS-Hyper-H patients showed significantly lower LS BMD and tended to show lower FN BMD values, as compared to those with hypogonadotropic hypogonadism (Hypo-H). In KS men, LS BMD was significantly lower than in those with non-KS-Hyper-H. No significant differences in the prevalence of vertebral fractures were found between the groups. Conclusions: These findings suggest a potential negative effect of FSH excess on the male bone mass, especially at spine. The duration of high FSH levels may also contribute to these findings.